Hydrogeochemical sources and enrichment mechanisms of trace elements in river water of a typical endorheic headwater region on Tibetan Plateau - Jie Wang; Yong Xiao; Yuqing Zhang; Wenxu Hu; Zexue Qi; Xiangzhi You; Xiaofan Gu; Huizhu Chen; Jibin Han; Yongxing Zhang; Liwei Wang (Applied Water Science)
Abstract Trace elements, such as lithium (Li) and boron (B), hold significant economic value for human community development and are commonly enriched in river water of the headwater regions of endorheic salt-lake basins. Understanding their sources and enrichment mechanisms is vital for both sustainable salt-lake resource exploitation and freshwater resource security. The Golmud River watershed, a typical hyper-arid endorheic basin on Tibetan Plateau, was investigated to explore the hydrogeochemical characteristics of river water in headwater regions of salt-lake basins, as well as the sources and enrichment mechanisms of trace elements. The results indicate that the hydrochemical types of river water in the headwater regions are predominantly HCO3-Ca, Cl-Na, as well as their mixed types. River water hydrochemical components are primarily controlled by rock-water interactions, with minor influence from evaporation. The interacting substances include halite, sulfate minerals, and calcite, sourced from silicate rocks and evaporites. Li and B are highly enriched trace elements in river water of the watershed, exhibiting similar spatial distributions, with the same natural origin. Trace elements in the watershed derive primarily from three sources, including rock-water interactions in Quaternary sediments (PC1), deep magmatic inputs via geothermal fluids (PC2), and permafrost thawing (PC3). PC2 dominates trace element enrichment in river water of the headwater region (83.9%), controlling Sr, U, B, and Li. PC1 primarily governs Co, Ni, Cu, Ba, and W (11.1%), while PC3 regulates Cr and Pb (5.0%). This work elucidates key sources, contributions and enrichment processes of trace elements in river water of the headwater region of arid endorheic salt-lake basins.